Preventing "Negative Responses" to scientific publication policies / Argo Pambudi - Argo, Pambudi (2021)
This paper aims to reveal the facts about the many "negative responses" to the scientific publication policies of universities in Indonesia in particular, and in developing countries in general. The purpose of the policy is very noble, to improve the performance of academics, to improve the performance of higher education institutions, to ensure the quality of education, and to protect the public from disgraceful practices in the administration of higher education. However, empirical facts and facts from previous research show symptoms that the negative response to the publication policy has damaged the academic order and degraded the reputation of higher education academics in general (Demir, 2018d; Macháček & Srholec, 2021; Kurt, 2018; Simón, 2016; Lukic et al., 2014; Xia, Harmon, Connolly, Donnelly, Anderson, Howard, 2014; Xia, 2015; Knudson, 2014; Gasparyan, Yessirkepov, Diyanova, & Kitas, 2015). This problem does not only occur in the national scope of one country but also occurs in many countries. It even involves international networks in many of these countries. Furthermore, until now there has been no action from the governments in the relevant countries that has countered this negative response. Let alone lost, the negative response of the community is increasing and causing material and non-material losses that are not small. The most worrying result is the damage to the reputation of universities and their products. The initial idea of writing this paper was triggered by many of these problems. Even if there is already a policy from the government to counteract these problems, its implementation has not resulted in improvements as expected.